(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2020)
The article aims to analyze the possibility of applying dogmatic constructions about formal and material typicality to the scope of administrative improbity, drawing parallels between the sanctioning penal and administrative system, as well as observing some resonances in Brazilian doctrine and jurisprudence. After retaking the concepts of type, typification and typicality, as well as defending its applicability to the area of Act nº 8.429/1992, the study points out, from the perspective of formal typicality, some problems of taxativity in the description of misconduct and the relevance of strict prediction of applicable sanctions. Finally, it is defended as necessary the appreciation of the material aspect of acts of administrative improbity, being indispensable to the configuration of the illicit significant violation to the assets and values protected by Act nº 8.429/1992, under penalty of distortion of its sanctioning system, however, highlighting the need for the adoption of stable criteria for the application of the principle of insignificance.